2014
DOI: 10.1155/2014/923135
|View full text |Cite
|
Sign up to set email alerts
|

Polarization of ILC2s in Peripheral Blood Might Contribute to Immunosuppressive Microenvironment in Patients with Gastric Cancer

Abstract: Newly identified nuocytes or group 2 innate lymphoid cells (ILC2s) play an important role in Th2 cell mediated immunity such as protective immune responses to helminth parasites, allergic asthma, and chronic rhinosinusitis. However, the contributions of ILC2s in the occurrence and development of cancer remain unknown. Our previous study found that there was a predominant Th2 phenotype in patients with gastric cancer. In this study, the ILC2s related genes or molecules in PBMC from patients with gastric cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(89 citation statements)
references
References 27 publications
(28 reference statements)
1
81
0
Order By: Relevance
“…The growing field of ILC research is still in its infancy for human cancers (41,42), although some recent studies reported on ILCs in murine tumor models. ILC1, and potentially ILC3, may be involved in tumor immunosurveillance (43,44).…”
Section: Discussionmentioning
confidence: 99%
“…The growing field of ILC research is still in its infancy for human cancers (41,42), although some recent studies reported on ILCs in murine tumor models. ILC1, and potentially ILC3, may be involved in tumor immunosurveillance (43,44).…”
Section: Discussionmentioning
confidence: 99%
“…In a model of breast cancer, exogenous IL-33 drove a mixed regulatory/type 2 immune infiltrate that promoted tumor growth and metastasis (Jovanovic et al, 2013). Elevated levels of blood ILC2s were identified in patients with gastric cancer and were associated with a suppressive immune state (Bie et al, 2014). Together, the effects of IL-33 on cancer appear context-specific, and may depend on the types of immune cells in the tumor environment, the amount of available IL-33, the amount of sST2 and the tumor cell-intrinsic expression of ST2L.…”
Section: Il-33-st2 In Infection and Non-allergic Inflammationmentioning
confidence: 99%
“…Despite their residency properties, a few ILCs have been reported to circulate in human blood. Thus, increased frequencies of ILC1s and ILC2s were found in patients with colorectal cancer (59) and with gastric cancer, respectively (60,61). RORγt + ILC3s were also reported to migrate via the bloodstream toward the tumor site in response to CCL21 in mouse models of breast cancer (37) and in melanoma (62).…”
Section: Ilcs In the Tumor Site: Migration Vs Local Expansionmentioning
confidence: 98%
“…In human lung cancer, a NCR + population of ILC3s was found to accumulate at the edge of lymphoid structures in the tumor tissue (37,62,63). An enrichment of ILCs in tumors compared to healthy tissue has also been observed for ILC1s in gastrointestinal tumors (49) or ILC2s in gastric, breast and prostate cancer (34,49,60). Despite the presence of ILCs in the above-mentioned types of cancer, whether they contribute to the underlying pathology in humans is still a matter of debate.…”
Section: Ilcs In the Tumor Site: Migration Vs Local Expansionmentioning
confidence: 99%